2018
DOI: 10.1093/ons/opy065
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Posterior Polyethylene Tethers to Prevent Proximal Junctional Kyphosis After Multilevel Spinal Instrumentation for Adult Spinal Deformity

Abstract: Junctional tethers significantly reduced occurrence of PJK. This difference was progressive from NT to TO to TC, but only reached pairwise significance for NT vs TC. This suggests potential benefit of tethers to reduce PJK, and that future prospective studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…The effect of tethers may be lessened when the UIV is at the mid-to-upper thoracic spine. Furthermore, Buell et al 38 attached the tether to a crosslink at the UIV for some of their patients, which was associated with an even lower rate of PJK in a pilot study by the same authors. Thus, the efficacy of the surgical technique, with regard to level placement, use of crosslinks, and method of tensioning, will require continued investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of tethers may be lessened when the UIV is at the mid-to-upper thoracic spine. Furthermore, Buell et al 38 attached the tether to a crosslink at the UIV for some of their patients, which was associated with an even lower rate of PJK in a pilot study by the same authors. Thus, the efficacy of the surgical technique, with regard to level placement, use of crosslinks, and method of tensioning, will require continued investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management of ASD is often associated with high blood loss and transfusion requirements. 2,4,5,25,[36][37][38] The significant blood loss and transfusions may be related to several factors, such as the relatively advanced age of many patients with ASD, their high rate of associated comorbidities, as well as surgically related factors (i.e., posterior approach, pelvic fixation, osteotomy, and longer operative duration). 26,42 The need for blood transfusions to compensate for these losses is associated with perioperative complications such as infections, thromboembolic events, and hemolytic transfusion reactions.…”
Section: Discussionmentioning
confidence: 99%
“…A finite element analysis by Bess and colleagues suggested that tethers are effective in dissipating the forces at the uppermost instrumented vertebra (UIV), 3 and recent case series support their clinical effectiveness in reducing PJK. 7,8 The magnitude and location of correction of LL also appear to be important factors in PJK development. It is important to apply age-adjusted alignment objectives when planning ASD surgery to reduce the risk of overcorrection of LL, which may produce excessive compensatory junctional kyphosis.…”
Section: Pseudarthrosis and Instrumentation Failurementioning
confidence: 99%